(untitled) (Bangladesh Journal of Physics, 2025)
The metallic glass with composition Fe30Ni50B20 in the form of ribbon has been prepared by rapid solidification using a melt spinning technique at a wheel speed of 25 m/s in Ar atmosphere. This ribbon has been studied based on different annealed effects in associated structural kinetics and activation energy using Differential Thermal Analysis (DTA) and XRD analysis. The impact of annealing in the range of 200 °C to 400 °C with two steps constant annealing time has been compared with its amorphous states by DTA and XRD techniques. From DTA experiments, one exothermic peak, α-Fe(Ni) is found which is responsible for the softness of metallic glass ribbon at as-cast state and with increasing annealing temperature, the peak temperature of α-Fe(Ni) phase shifts toward higher temperature which agrees well with the XRD patterns. The activation energy of the annealed and as-cast ribbon samples is obtained within the range of 3.30 to 3.91 eV. In the optimized annealing temperature above 350 °C, the grain size obtained from XRD patterns in the range between 8-29 nm and the lattice parameter shifts to higher values with increasing annealing temperature as well as with constant holding time. The desired initial permeability below the glass transition temperature of the metallic glass ribbon depends on the best choices of parameters and its annealing effects with constant annealing time. Bangladesh Journal of Physics, 28(1), 25-38, June 2021